Translation, Cultural Adaptation and Validation to Brazilian Portuguese of the Tinnitus Functional Index Questionnaire - Rosa, Marine Raquel Diniz da; Doi, Marcelo Yugi; Branco-Barreiro, Fátima Cristina Alves; Simonetti, Patricia; Oiticica, Jeanne; Marchiori, Luciana Lozza de Moraes (International Archives of Otorhinolaryngology, 2021)
Introduction Tinnitus affects a large portion of the world's population. There are several questionnaires being used for the evaluation of the severity of tinnitus and its impact in quality of life; however, they do not measure treatment-related changes. So, a new self-reported questionnaire was developed, the Tinnitus Functional Index (TFI), which has been translated into several languages.Objective To perform the translation, cultural adaptation and validation of the TFI questionnaire for Brazilian Portuguese.Method This is a multicenter project divided into two stages: translation and cultural adaptation; and validation and reliability. For the validation, the Brazilian Portuguese version of the TFI was correlated with the Tinnitus Handicap Inventory (THI) domains for tinnitus and quality of life and was evaluated by the Spearman ρ test. The reliability and internal consistency were evaluated by the Cronbach α test.Result The Brazilian version of the TFI was obtained through an initial translation process, synthesis of translations, backtranslation and evaluation by a committee of experts. This version was then applied in 88 patients complaining of tinnitus from speech therapy and otorhinolaryngology outpatient clinics of the three school clinics. The Brazilian version presented high reliability, as evidenced by the Cronbach α value (α = 0.870), and strong correlation (rho = 0.760 and p = 0.000).Conclusion The high reliability found in the results demonstrates that the Brazilian Portuguese version of the TFI is a valid and reliable instrument to evaluate the severity and impact of tinnitus on quality of life and changes related to its treatment.
Keywords: tinnitus; questionnaires; validation studies